Legal Protection Of Consumers Against Indonesian National Standards In Buying And Buying LPG Gas - Husein, Zidan Ahmad; Fajri, Ibrahim; Purwaningsih, Prihatini (Universitas Ibn Khaldun Bogor, 2025)
In the current era of globalization and modernization, consumers are faced with various complex challenges and risks, there are many forms of violations by business actors in buying and selling LPG gas. Then we need to know what legal protection there is for consumers when buying and selling LPG gas. This research aims to determine legal protection for consumers and distributors in using products with SNI labels, for consumer safety. The data collection used in this research is library research. In this research, normative juridical research is used. This type of research is carried out by examining library materials or secondary data consisting of primary legal materials and secondary legal materials. This research will utilize various primary, secondary and tertiary legal data sources. Violations in the practice of buying and selling LPG gas in the form of SNI cylinders often involve various forms of non-compliance with established regulations. Such as filling in illegally and falsifying certificates. Of course, this is very disturbing for consumers who use LPG gas, therefore Law Number 8 of 1999 concerning Consumer Protection contains legal regulations regarding protection for consumers against violations by business actors in buying and selling LPG gas. As well as resolving disputes if consumers feel disadvantaged